ANALISA PERBEDAAN ECO-FRIENDLY ATTITUDE DAN ECO-FRIENDLY INTENTION ANTARA TURIS LOKAL DAN TURIS ASING TERHADAP GREEN - Jokom, Regina; Kristanti, Monika (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2014)
The increasing concern for environmental degradation caused many people to pay more attention to theÃ‚Â green practice in the industry including hotel. Majority of hotel chains have adopted environmental programs andÃ‚Â labeled as green hotel.Ã‚Â This study examines the significant differences between local tourist and foreign tourist regarding ecofriendlyÃ‚Â attitude and eco-friendly intention toward green hotel. Questionnaires were distributed to 120 localtourists and 120 foreign tourists In Juanda International Airport Surabaya. The study reveals that there areÃ‚Â significant differences in severity of environmental problems, intention to stay, intention to spread positive wordÃ‚Â of mouth, and intention to pay extra for green hotel between local and foreign tourist.Keywords: eco-friendly attitude, eco-friendly intention, green hotel, hospitality